Tailored biosecurity training for veterinarians and farmers: bridging knowledge and practice gaps - Mehmedi, Blerta; Niemi, Jarkko; Saegerman, Claude; De Meneghi, Daniele; Iatrou, Anna Maria; Yildiz, Ramazan; Chantziaras, Ilias; Allepuz, Alberto; Toppari, Ina; Batikas, Georgios; Viltrop, Arvo; Niine, Tarmo (Frontiers in Veterinary Science, 2025)
Biosecurity is fundamental to animal health, public health, and the economic resilience of livestock systems; however, farm-level adoption remains uneven across regions. Knowledge gaps, language and financial constraints, and limited communication competence among veterinary advisers impede implementation, especially on small- and medium-scale farms. Behavior change-oriented interventions, such as Motivational Interviewing (which deploys multiple specific behavior change techniques as defined in BCTTv1), offer promise but are seldom embedded in veterinary curricula. This study proposes a concept and key elements for biosecurity training. It highlights a modular, evidence-based training framework developed under the COST Action CA20103 “BETTER” (2021–2025), aimed at improving biosecurity understanding and implementation by veterinarians and farmers. The initiative convened European experts to co-design a flexible curriculum that addresses both technical and behavioral challenges using participatory methods and interdisciplinary expertise. The resulting framework consists of five progressive modules: (1) Introduction, (2) Behavior Change and Communication, (3) Disease Transmission & Risk Assessment, (4) Emergency Response & Clinical Biosecurity, and (5) On-Farm Practices. These modules are designed to be combined in a “pick-and-choose” format to match local needs, target audiences and resources. Delivery blends online micro-lessons, participatory workshops, peer networks, and low-cost on-farm demonstrations, while materials are culturally and linguistically adapted and framed in terms of clear economic benefits. Continuous feedback loops encourage iterative refinement and habit formation during the learning process. The proposed training framework seeks to transform biosecurity from a prescriptive doctrine into a farmer-owned daily routine by integrating technical content with behavioral science and context-specific delivery.